2006
DOI: 10.1287/mnsc.1060.0542
|View full text |Cite
|
Sign up to set email alerts
|

Value Implications of Investments in Information Technology

Abstract: The year 2000 (Y2K) countdown provided a uniquely visible instance of spending on information technology (IT) by U.S. companies. With public attention riveted on potential Y2K malfunctions, managers were forced to evaluate their IT and make decisions about whether to modify or replace existing systems. In the aftermath of Y2K, critics charged that the problem was overblown and that companies overspent on IT. In contrast, we posit in this paper that efforts companies made to renew and upgrade their IT may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 42 publications
1
83
0
2
Order By: Relevance
“…Value is rarely calculated in quantitative measurements because it is considered a complex, dynamic and context-dependent variable that is subject to the type of company and researcher carrying out the estimate (Anderson, et al 2006). …”
Section: Fig 2 -The Enterprise Governance Of Itmentioning
confidence: 99%
“…Value is rarely calculated in quantitative measurements because it is considered a complex, dynamic and context-dependent variable that is subject to the type of company and researcher carrying out the estimate (Anderson, et al 2006). …”
Section: Fig 2 -The Enterprise Governance Of Itmentioning
confidence: 99%
“…The impact of IT resources on operational capability can be explained mainly by the strategic roles that IT resources play in business organizations-the standardization [21] and automation. The most essential and significant role of IT is to automate business processes that traditionally have been driven mostly by paper handling and therefore tended to be laborious and error-prone [5]. Hence, given the large number of transactions a government agency usually handles, the value impact of automating business processes can be enormous.…”
Section: The Analytical Framework Of It's Effects On Public Service Pmentioning
confidence: 99%
“…It has been one of the primary research focuses on information systems literature for the last couple of decades to find whether information technology investments can lead an organization to generate greater productivity and achieve sustainable competitive advantages [2]. A large number of empirical evidences have shown that information technology is positively associated with organizational productivity, profitability, and market value [3,4,5]. A subsequent question raised is how investments in IT lead to greater organizational productivity in public service.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, McAfee and Brynjolfsson (2008, p. 103) found out in an extensive study that "IT appears to be much more strongly correlated with the changes in the competitive dynamics than R&D does." The controversial discussion about the actual contribution of IT to business performance (Anderson et al 2006;Lim et al 2004) is also reflected in the results of numerous studies on the implementation of CRM systems. Whereas on the one hand the failures of CRM projects have mainly been attributed to technological aspects (e.g.…”
Section: Mutual Alignment Of Marketing and Itmentioning
confidence: 99%